Prevention of autoimmune diabetes and islet allograft rejection by beta cell expression of XIAP: Insight into possible mechanisms of local immunomodulation. (5th December 2018) - Obach, Mercè; Hosseini-Tabatabaei, Azadeh; Montane, Joel; Wind, Katarina; Soukhatcheva, Galina; Dai, Derek; Priatel, John J.; Orban, Paul C.; Verchere, C. Bruce
Abstract: Overexpression of the X-linked inhibitor of apoptosis (XIAP) prevents islet allograft rejection. We constructed an adeno-associated virus expressing XIAP driven by the rat insulin promoter (dsAAV8-RIP-XIAP) for long-term beta-cell gene expression in vivo . Pancreatic delivery of dsAAV8-RIP-XIAP prevented autoimmune diabetes in 70% of non-obese diabetic (NOD) mice, associated with decreased insulitis. Islets from Balb/c mice transduced with dsAAV8-RIP-XIAP were protected following transplantation into streptozotocin (STZ)-diabetic Bl/6 recipients, associated with decreased graft infiltration. Interestingly, dsAAV8-RIP-XIAP transduction induced expression of lactate dehydrogenase (LDHA) and monocarboxylate transporter 1 (MCT1), two genes normally suppressed in beta cells and involved in production and release of lactate, a metabolite known to suppress local immune responses. Transduction of Balb/c islets with AAV8-RIP-LDHA-MCT1 tended to prolong allograft survival following transplant into STZ-diabetic Bl/6 recipients. These findings suggest that XIAP has therapeutic potential in autoimmune diabetes and raise the possibility that local lactate production may play a role in XIAP-mediated immunomodulation. Graphical abstract: Highlights: XIAP is an anti-apoptotic factor whose overexpression in beta cells has been shown to prolong islet allograft survival. XIAP overexpression in beta cells using adeno-associated virus reduced autoimmune diabetes in NOD mice by 70%. XIAP overexpression in beta cells is associated with expression of LDHA and MCT1, and lactate production. Lactate production by beta cells did not significantly promote islet allograft survival nor ameliorate autoimmune diabetes.